Pembuatan Game Pembelajaran Mengenal Alat Transportasi Berbasis 3D di TK Pertiwi II Kecamatan Jepon â Blora - Sutrisno, Sutrisno; Purwanti, Dwi (Edu Komputika Journal, 2016)
The purpose of this study was to determine the process development and feasibility study media model of mobile learning (m-learning) and find out what interests the tenth grade students majoring in Computer Engineering and Networks (TKJ) to study media mobile learning (m-learning) at SMK NU Ungaran on the eyes teaching basic network. Media development stages: (1) Potential and Problems, (2) Product Design, (3) Preparation Products, (4) Product Validation, (5) Test da Creative Media Specialist, (6) test the student response has been (7) conclusions. The object of this research is the development of m-learning instructional media on the subject matter of basic network. The data collection is done by using a questionnaire (questionnaire). Data analysis technique is done with descriptive percentage by test experts and media by a team of experts, while interest by students of class X TKJ majors. The results of this study are in the form of m-learning instructional media. Instructional media declared eligible by the feasibility test products according to media expert with eligibility percentage of 77.40%, an expert assessment of the material with a percentage of 85.11%. As for the response test students get a percentage of 79.28%. Media learning to m-learning has proven its effectiveness. From the test results can be concluded that the m-learning instructional media developed a decent used mainly to support the learning process on the subjects of the basic network.